Socjalizacja i wychowanie. W poszukiwaniu genezy wychowania (perspektywa ewolucyjna) - Muszyński, Heliodor (Kultura-Społeczeństwo-Edukacja, 2022)
The author deals with the problem of differences in meaning between the concepts of socialization and education. In social sciences, and especially in educational sciences, there is no agreement as to the relationship between the scopes of these two fundamental concepts. The article attempts to overcome these semantic difficulties by adopting an evolutionary perspective in line with the assumption that education emerged as a specific type of socialization in human prehistory. The search of its essential properties (and thus differences), was guided by the cognitive directive of Aristotle, according to which “the best understanding of things is achieved by those who study them at their inception”. The article uses the method of data analysis established in numerous studies on social and cultural human development, starting from the earliest stages of life in primitive groups. Socialization appeared in these groups as a way of transmitting collective experience, and thus culture, necessary for their survival. The continuation of the analysis leads to investigating what factors made this culturation take a different form, namely that of education. As it turns out, this difference is difficult to discern in the intentionality of cultural influences. It appears only when the group becomes aware of the need to adapt adolescents to fulfill various social roles. This already requires going beyond socialization, which is always a spontaneous process including widespread participation of group members in the transmission of an experience that is also common. In order to provide selected group members with selected elements of the experience linked to their social role, the group must appoint competent members for the transfer of the experience selected to perform specific social roles. These activities constitute one more role distinguished in the group – the role of the educator. And the activities that make up their performance are education.